Jacobi Elliptic Monopoleantimonopole Pair Of The Su(2) Yang-Mills-Higgs Theory - Tan, Pei Yen (2013)
Magnetic monopoles and multimonopole are well known three dimensional topological soliton solutions of the non-Abelian SU(2) Georgi-Glashow model. They are remnants of the spontaneous symmetry breaking of the gauge group SU(2) into the group U(1) with net magnetic charge. In this thesis, the SU(2) Georgi-Glashow model or synonymously SU(2) Yang- Mills-Higgs theory is studied to seek for more magnetic monopole configurations along with their properties at the classical level. To find such configurations in the model, one need to substitute a suitable ansatz into the second order equations of motions and look for an analytical or numerical solutions. The axially symmetric Jacobi elliptic one-monopole (Teh et al. 2010) configurations were obtained by generalizing the large distance asymptotic solutions to the Jacobi elliptic functions and solving the second order field equations numerically. We study them numerically by varying its magnetic number and analyze its properties when the Higgs potential is non-vanishing. These are non-BPS, regular solutions which possess the same total energy as the generalized ’t Hooft-Polyakov monopole. Some of these monopoles are distorted and possess magnetic dipole moment.